Pembiasaan Literasi Numerasi dalam Pembelajaran Matematika di MA Al-Mahrusiyah - Anis Suraida Safitri (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Numeracy literacy has not been applied optimally so that the numeracy literacy score of students from PISA is low. The low numeracy literacy skills can be overcome by organizing learning that facilitates students to have numeracy literacy. The research objectives in this study are: 1) to describe mathematics learning strategies in numeracy literacy habituation. 2) to describe the interaction of students and teachers in habituation of numeracy literacy. The type of research used by researchers is qualitative research. This research was conducted at MA Al-Mahrusiyah class X (Phase E) in the first semester of the 2022/2023. Data collection techniques were carried out by collecting documents, collecting theories, interviewing math teachers, direct observation and administering questionnaires. Data validity with triangulation. Data analysis techniques using two ways, namely data reduction, data presentation and conclusions. The results of this study are: (1) numeracy literacy habituation has been running following three stages of literacy, namely: habituation, development and learning. Learning activities have implemented a variety of models. The learning modules prepared can facilitate students in the learning process and find concepts. The evaluation questions used focus on HOTS with various forms of questions, (2) habituation of numeracy literacy requires the activeness of students and the creativity of teachers in designing learning. In math learning activities, there are two activities, namely independent controlled training and group controlled training. Abstrak Literasi numerasi belum diterapkan secara maksimal sehingga skor literasi numerasi peserta didik dari PISA rendah. Rendahnya kemampuan literasi numerasi bisa diatasi dengan penyelenggaraan pembelajaran yang memfasilitasi peserta didik untuk berliterasi numerasi. Tujuan penelitian pada penelitian ini yaitu: 1) mendeskripsikan strategi pembelajaran matematika dalam pembiasaan literasi numerasi. 2) mendeskripsikan interaksi peserta didik dan guru dalam pembiasaan literasi numerasi. Jenis penelitian yang digunakan peneliti yaitu penelitian kualitatif. Penelitian ini dilaksanakan di MA Al-Mahrusiyah kels X (Fase E) pada semester ganjil tahun pelajaran 2022/2023. Teknik pengumpulan data dilakukan dengan mengumpulkan dokumen, mengumpulkan teori, wawancara guru matematika, observasi langsung dan pemberian kuesioner. Keabsahan data dengan triangulasi. Teknik analisis data dengan menggunakan dua cara yaitu reduksi data, penyajian data dan kesimpulan. Hasil penelitian ini yaitu: (1) pembiasaan literasi numerasi telah berjalan mengikuti tiga tahapan literasi, yaitu: pembiasaan, pengembangan dan pembelajaran. Kegiatan pembelajaran telah menerapkan model yang bervariasi. Modul pembelajaran yang disusun dapat memfasilitasi peserta didik dalam proses belajar dan menemukan konsep. Soal evaluasi yang digunakan terfokus pada HOTS dengan berbagai bentuk soal, (2) pembiasaan literasi numerasi membutuhkan keaktifan peserta didik dan kekreatifan guru dalam merancang pembelajaran. Dalam kegiatan pembelajaran matematika terdapat dua kegiatan yaitu pelatihan terkontrol mandiri dan pelatihan terkontrol kelompok.